Surface plasmon resonance in extracellular vesicle-cell interaction studies : Differential uptake of red blood cell, platelet and PC-3 cell –originated extracellular vesicles into PC-3 prostate cancer cells - Koponen, Annika (fi=Turun yliopisto|en=University of Turku|, 2017)
Cells react to different stimuli by secreting membrane composed extracellular vesicles (EVs). EVs mediate intercellular communication and hence participate in many physiological and pathological processes. Their ability to carry functional molecules has awoken growing interest on their use as drug vehicles in therapeutical applications. The mechanisms and dynamics of EV uptake into their target cells is however still relatively poorly understood. Conventional methods to study the EV uptake are limited on providing only the end-point data by using fluorescent labels. Hence, new techniques to investigate EV internalization in real-time without labels are desirable. The aim of this study was to provide a comprehensive description of a novel approach on EV uptake studies using surface plasmon resonance (SPR) -based method to monitor cellular internalization in real-time without labels. Furthermore, the possible differences in the internalization of red blood cell, platelet and autologous EVs into PC-3 prostate cancer cells was investigated. Nano particle tracking analysis, western blot, zeta potential and total protein content measurements were used to reveal the characteristics of the studied EVs. A real-time label-free approach using SPR was utilized to study the interactions of EV with PC-3 cells. Confocal imaging was performed to confirm EV uptake into the studied target cells. The results of this study suggest that EVs isolated from distinct sources differ by their characteristics and by the cellular responses they induce in PC-3 prostate cancer cells. It was concluded that SPR is a potential method to be used in EV uptake studies as a complementary method for conventional studies. This study brings novel insights on EVs uptake both from a biological and a methodological viewpoint and arises appealing questions for further studies.